Geochronology and timescales in the evolution of mammalian tooth shape: the Paleogene of Patagonia - Madden, R. H. (2010)
The South American fossil record provides a unique and rich record of the evolution of mammalian tooth shape, especially structural features that serve to resist abrasive wear. For the evolution of mammalian tooth shape, our understanding of geochronology points increasingly to a convergence between rates of morphological change and the intensity of earth surface processes (climate-driven erosion of pyroclastic sediment accumulations). Using single zircon U-Pb methods to construct high-precision age models for fossil-bearing strata of the Sarmiento Formation, we gain increasing confidence in the remanent magnetic polarity stratigraphy and the measurement of linear sedimentation rates.